Developing a self-regulating soldering iron based on induction heating (2016)
This work focused on the design, development and construction of a new low cost soldering iron that works by means of induction heating. The amount of electronic components has been minimized in order to reduce production costs. Additional tests were undertaken to determine the ideal tips for soldering, and the adaptations necessary to guarantee self-regulation using a nickel foil shield (due to its low curie temperature) are suggested. The new device contains a resonant inverter able to generate alternating magnetic fields of 100 kHz at the center of an 18-turn coil; the inverter is controlled only using an astable oscillator circuit. The paper examines criteria to select suitable soldering-tips by experimentally determining their equivalent resistance heating it within the resonant inverter or well, another one by using a rapid magnetic test. The system represents a good tool, suitable for the manufacture of development boards or electronic tasks.